2014
DOI: 10.7205/milmed-d-13-00400
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Combat Experiences and Alcohol Misuse Among U.S. Special Operations Soldiers

Abstract: This study examined the association between specific combat experiences and postdeployment hazardous drinking patterns on selected military populations that are considered high risk, such as personnel belonging to U.S. Army Special Operations Forces. Data collection were conducted in a 5-year span in which 1,323 Special Operations Forces Soldiers were surveyed anonymously from 3 to 6 months after returning from deployment to Iraq/Afghanistan regarding their combat experiences and mental health. Combat items we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…Suicide ideation was reported by 3.3% ( n = 31) and aggression was reported by 52.2% ( n = 493). Cutoffs for alcohol misuse (Skipper et al., ) were met by 39.9% ( n = 377), and risk‐taking behaviors were reported by 13.8% ( n = 130). Cutoffs for depression (Kroenke et al., ) were met by 7.6% ( n = 72), and sleep problems were reported by 19.0% ( n = 179).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Suicide ideation was reported by 3.3% ( n = 31) and aggression was reported by 52.2% ( n = 493). Cutoffs for alcohol misuse (Skipper et al., ) were met by 39.9% ( n = 377), and risk‐taking behaviors were reported by 13.8% ( n = 130). Cutoffs for depression (Kroenke et al., ) were met by 7.6% ( n = 72), and sleep problems were reported by 19.0% ( n = 179).…”
Section: Resultsmentioning
confidence: 99%
“…Cronbach's alpha for the AUDIT‐C was 0.79. A dichotomous variable was created to analyze alcohol misuse; a positive score indicated the criteria for alcohol misuse had been met (i.e., a score ≥5 for males or ≥4 for females; Skipper, Forsten, Kim, Wilk, & Hoge, ).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies and reviews have shown that higher combat exposure is significantly associated with postdeployment mental health issues (Hoge, Auchterlonie, and Milliken, 2006;Sareen et al, 2007;Skipper et al, 2014;Ramchand, Schell, Karney, et al, 2010;Ramchand, Rudavsky, et al, 2015), and significant percentages of recently deployed service members report mental and physical health problems-including PTSD, TBI, generalized anxiety, and major depression-that may stem from their combat exposures (Tanielian and Jaycox, 2008;Hoge, McGurk, et al, 2008). Other studies have associated combat exposure with chronic pain (Sheffler et al, 2016) and increased dependence on substances, particularly alcohol (Ramchand, Rudavsky, et al, 2015;Wilk, Bliese, Kim, et al, 2010) and prescription drugs (e.g., opioids) (Seal et al, 2012;Toblin et al, 2014).…”
Section: Combat Experiences During Deploymentmentioning
confidence: 99%
“…Several studies have explored the relationship between combat exposure and substance use and misuse (Jeffery and Mattiko, 2016;Jacobson, Ryan, et al, 2008;Santiago et al, 2010;Skipper et al, 2014). Jacobson, Ryan, and colleagues (2008) found that service members who deployed and reported combat exposure were at increased risk of alcohol misuse (i.e., new onset of drinking, binge drinking, and alcohol dependency).…”
Section: Deployment and Substance Usementioning
confidence: 99%
“…Objective assessment of intensity of HCWs’ stressor exposure during the COVID-19 pandemic is based on acquiring information from official hospital archives and clinical records regarding their daily schedules during the COVID-19 pandemic, overtime work, the level of threat they experienced, sick leave, etc. These objective metrics of exposure to stressors are proposed based on analysis and adaptation of different questionnaires that have been used for assessment of stressors in military combat deployment and operation ( 22 - 24 ), as well as stressors in virus outbreaks ( 25 - 28 ). The key aim of this phase is to objectively stratify individual HCWs according to the objective level of stress to which they were exposed during their clinical service, using the information provided by authorized clinical sources rather than by asking individuals to self-report themselves.…”
Section: Proposed Methodologymentioning
confidence: 99%